Light-induced epigenetic modifications in the hypothalamus during avian embryonic development enhance phenotypic plasticity - Bartman, Joanna; Rosenberg, Tali; Parnas, Hadar; Yosofov, Ronit; Avital-Cohen, Natalie; Weiss, Ron; Harmatz, Gal; Rozenboim, Israel; Marco, Asaf (Frontiers in Cell and Developmental Biology, 2025)
IntroductionEarly brain development is highly sensitive to environmental cues, which can exert lasting phenotypic effects. Targeted external interventions during this critical period can shape developmental trajectories and influence an animal’s phenotype. Aligned with this concept, fetal responses to light-induced stimuli—varying in wavelength, frequency, and duration—are thought to facilitate adaptive reactions that enhance phenotypic plasticity and equip organisms to meet environmental challenges.MethodsIn this study, broiler eggs were exposed to green monochromatic illumination (GMI) either continuously throughout incubation (Green) or during the final 3 days only (G3D) and compared to dark and white light controls.ResultsGenome-wide analyses revealed significant transcriptional changes in the hypothalamus of the G3D group, identifying over 500 differentially expressed genes related to growth, metabolism, appetite, and immunity. Epigenetically, GMI exposure increased phosphorylated CREB1 (pCREB1) binding levels and chromatin accessibility at specific gene promoters, underscoring the role of light-induced developmental programming. Notably, these effects were exclusive to the G3D group, highlighting the last 3 days of incubation as a critical window for intervention. In G3D, cFOS immunostaining revealed heightened hypothalamic responsiveness to a post-hatch green light pulse, indicating that in-ovo GMI primed the brain’s circuitry for future stimuli. Mechanistically, our findings suggest that GMI-induced hypothalamic adaptations are mediated, at least partially, through retinal green photoreceptors. Pre-exposure to blue light, which disrupts green photoreceptor activity, reduced retinal green opsin levels and nullified the epigenetic changes typically observed in the G3D group. Last, G3D chicks exhibited enhanced growth and improved food conversion ratios (FCR), particularly during early post-hatch development. Consistent with our transcriptomic and epigenetic data, the BG6D group showed no significant changes in body weight or FCR.DiscussionCollectively, these findings highlight how specific wavelengths and precise timing of light exposure during embryogenesis can shape post-hatch phenotypes through transcriptional and epigenetic mechanisms.